(untitled) (Journal of the College of Basic Education, 2026)
The research deals with the Age of Enlightenment and its scientific impact on the European scientific renaissance. The Age of Enlightenment is a philosophical movement whose ideas dominated Europe during the eighteenth century AD (and sometimes its beginning is traced back to the mid-seventeenth century). It was based on the idea that reason is the primary source of authority and legitimacy. The culture of the Age of Enlightenment was established in most European countries and cultural exchange took place between many European countries. The scholars of the Age of Enlightenment also presented many scientific achievements and discoveries that have had an impact to the present time. Therefore, the research was important in providing an overview of the Age of Enlightenment and the most important scientific discoveries and achievements, focusing on the impact of this era on the scientific renaissance in Europe. The research was divided into an introduction in which we presented the importance of the research, the reason for choosing it, the methodology, the time and place framework, and three chapters. The first chapter dealt with defining the Age of Enlightenment and its trends. The second chapter dealt with mentioning the most important scientific discoveries and achievements in various sciences. The third chapter discussed the impact of these discoveries and achievements on the scientific renaissance in Europe. The research ends with a conclusion in which the most important results reached by the research were presented.